Pengaruh Kualitas Layanan, dan Customer Relationship Management Terhadap Kepuasan Pasien dan Loyalitas Pasien di Rumah Sakit Tingkat II Tentara Nasional Indonesia - Sutrisno Sutrisno (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2015)
Indonesian National Army Hospitals (RS TNIs) is one of hospitals that servicing the Indonesian National Army (TNI) big family and public community. In the competitive and dinamics situation like today’s era, RS TNIs need to watch the change happened due to the policy change of health services in hospital. In 2014 there was happened the fundamental change of the health services in hospital related to the entry of National Health Insurance (JKN) into force that guarantes all Indonesian people. This change concerned to financial management, funding, membership, treatment procedures, types of services covered and not covered, referral system, pattern rates, claim, supervisory and evaluation. The number of regulatory changes in the new era of health care in Indonesia have trigered other changes, in particular hospital customer behavior. This case is interesting to study. Population in this research was the customers in 15 TNI’s hospitals in Indonesia, who have been treated twice or more in the TNI level two hospitals, at class 1, class 2 and class 3 treatment rooms. From the testing result on models in this research, by the Maximum Likelihood Estimates (ML), the analysis structural equation (SEM) model, the proportional random sampling method and the assistance of software Amos 22, on 200 respondents. The model testing (fit) of research data may viewed from GFI, AGFI, TLI, CFI, and RMSEA values, which respectively were 0.902, 0.904, 0.921, 0.952 and 0.0690. that all of those in the expected value range thus the model can be accepted. The research results indicated that: 1). Service quality is influential on customer satisfaction. 2). Service quality is influential on customer loyalty. 3). Customer relationship management is influential on customer satisfaction. 4). Customer relationship management is insignificantly influential on customer loyalty. 5). Customer satisfaction is influential on customer loyalty. Key words:      Service quality, CRM, Customer satisfaction, Customer loyalty.